Quantitative dependence of some discrete limiting classes on the Muckenhoupt A_1(u) class - Saker, S. H.; Mahmoud, R. R.; Hassan, M. H. (Ukrains’kyi Matematychnyi Zhurnal, 2023)
UDC 517.5 We prove some relations between the discrete Gehring classes G_q and the discrete Muckenhoupt classes A_p. Specifically, by using some known Hardy-type and Carleman-type inequalities, we study the relationship between G_1, A_∞ and A_1 for nonincreasing and nondecreasing weights. Finally, we establish some general results by introducing the notions of G_φ classes defined for nonnegative convex function φ.